Prediction of the electrical contact resistance endurance of silver-plated coatings subject to fretting wear, using a friction energy density approach - Laporte, J.; Perrinet, O.; Fouvry, S. (Wear, 2015)
Electrical connectors need to display low and stable electrical contact resistance (ECR). However, subjected to vibrations (engines, heat, etc.), fretting wear damages promotes the formation of insulating oxide debris and a sharp ECR increase decaying the information transmission. Noble plated coatings like silver layers are usually applied to delay the ECR failure. However, to predict such ECR endurance, it appears essential to determine the fretting wear rate. In the present study, a homogeneous crossed-cylinders Ag/Ag interface was investigated under gross slip conditions imposing various loading parameters (±2µm<δg<±16µm, 1N<P<6N, RH=10% and f=30Hz) for Ag layers from 1.7µm to 4.8µm. A global chemical investigation of the fretting scars confirms that ECR failure is reached when most of the silver is removed from the interface and an oxide debris layer is trapped in the contact. ECR endurance (Nc: ΔR>4mΩ) can be formalized, using a power law function of the mean friction energy density dissipated during a fretting cycle taking into account the contact area extension. Finally, a simple ECR endurance expression is derived as a function of the fretting loading parameters and the thickness of the silver plated layer. A very good correlation between experimental and predicted ECR endurances is achieved. •We studied the influence of the fretting wear on the electrical contact resistance.•Resistance degradation of an Ag/Ag contact is linked to the wear process.•Chemical analyses showed that concentrations influence the contact resistance values.•Friction energy density approach is used to predict the electrical failure.•A global formalization taking into account the loading parameters is expressed.